Preparation of Magnetic Photocatalyst Fe3O4@SiO2@Fe-TiO2 and Photocatalytic Degradation Performance of Methyl Orange in Na2SO4 Solution - Li Sun; Zilong Li; Zhigang Yuan; Ying Liu; Shunqi Mei; Fanhe Meng; Xingyu Ouyang; Yi Xiong; Ke Zhang; Zhen Chen (Applied Sciences)
In this study, Fe3O4@SiO2@TiO2 (FS-FT (0 g)) photocatalysts, featuring a magnetic core–shell structure, and Fe-doped Fe3O4@SiO2@Fe-TiO2 (FS-FT (x g)) photocatalysts, were fabricated via the sol–gel method. Structural and compositional analyses of the processed samples were systematically conducted through X-ray diffraction (XRD), transmission electron microscopy (TEM) with selected area electron diffraction (SAED), surface-sensitive X-ray photoelectron spectroscopy (XPS), and optical property assessment via UV-Vis diffuse reflectance spectroscopy (UV-DRS). The results show that TiO2 on the outer layer of FS-FT (0 g) and FS-FT (x g) has an anatase structure, and that Fe is doped into FS-FT (x g). The photodegradation of methyl orange (MO) using FS-FT (0 g) and FS-FT (x g) with various Fe doping levels was evaluated in both pure MO (C0 = 10 mg/L) and MO-Na2SO4-blended solutions. Under irradiation with high-pressure mercury lamps, the removal rates of MO using FS-FT (0 g) and FS-FT (0.36 g) in pure MO solution reached 90.25% and 99% at 25 min, respectively, which indicates that FS-FT (0.36 g) can enhance photocatalytic performance. The removal rates of MO using FS-FT (0 g) and FS-FT (0.36 g) in MO-Na2SO4-blended solution (C0 = 10 mg/L, CNa2SO4 = 12.5 g/L) reached 92.38% and 97.16% at 25 min, respectively. The removal rate of MO using FS-FT (0.36 g) decreased in MO-Na2SO4-blended solution in the previous 25 min, which indicates that Na2SO4 can inhibit degradation using FS-FT (0.36 g). The degradation experiments of MO-Na2SO4-blended solutions with different concentrations of Na2SO4 using FS-FT (0.36 g) showed that as the concentration of Na2SO4 increases, the inhibitory effect becomes more pronounced. Recovery and recycling experiments confirmed that the photocatalyst exhibited robust degradation performance over multiple cycles. Kinetic analysis of the photocatalytic data, based on a first-order model, was conducted to explore the underlying degradation principles.